Abiotic Stress Biology in Horticultural Plants - Kanayama, Yoshinori (Springer, 2015)
The purpose of this publication is to elucidate the biological aspect of the abiotic stress response from the field to the molecular level in horticultural plants. This book is unique in that it concerns the basic aspect of abiotic stress biology and research progress at the molecular level in model plants or major field crops, as it focuses mainly on the abiotic stress response in existing horticultural plants. Many readers interested in plant abiotic stress biology are aware of the application of the latest findings to agricultural production, and this book will have a special appeal for those readers. The book will be of interest to scientists and graduate students who are involved in the research, development, production, processing, and marketing of horticultural products, including those in developing countries who are interested in high tech and advanced science in this field. The application of the latest findings to agricultural production is particularly useful.